Highly active and selective supported rhenium catalysts for aerobic oxidation of n-Hexane and n-Heptane - Mishra, Gopal (2018)
A series of derivative C-scorpionate rhenium complexes, i.e., [ReCl2{NNC(O)C6H5} (Hpz)(PPh3)2] (A) (where Hpz is pyrazole), [ReCl2{NNC(O)C6H5}(Hpz)2(PPh3)] (B), [ReClF {NNC(O)C6H5}(Hpz)2(PPh3)] (C), and their precursor [ReOCl3(PPh3)2] (D), immobilized on 3-aminopropyl-functionalized silica have been prepared and used for neat O2 oxidation of n-hexane and n-heptane mainly to the corresponding alcohols and, in lower amounts, ketones. The supported catalyst C, with fluoro- and diazenido-ligands, exhibits the highest activity for both alkanes (overall turnover numbers (TONs) up to 3.8 _ 103 and 2.5 _ 103, for n-hexane and n-heptane, respectively) and can be reused in consecutive catalytic cycles. Improved conversion was observed after addition of hetero-carboxylate co-catalysts. A free-radical-based mechanism is proposed to explain the product formation.